Influence of Fetal and Maternal Genetic Susceptibility to Obesity on Birthweight in African Ancestry Populations - Shrestha, Deepika; Rahman, Mohammad L.; Workalemahu, Tsegaselassie; Zhu, Chunming; Tekola-Ayele, Fasil (Frontiers in Genetics, 2018)
Genetic and environmental factors modulate the life-cycle relationships of maternal pre-pregnancy obesity, offspring birthweight, and offspring risk of obesity during adulthood. Insights into the genetic influence in these relationships can inform efforts to curb the rising prevalence of obesity in early life; however, there is paucity of such studies, particularly in African ancestry populations. We investigated the effects of offspring and maternal genetic risk of obesity on birthweight and evaluated whether these genetic influences modify the well-known association between maternal pre-pregnancy body mass index (BMI) and birthweight. In 950 mother-baby pairs of African ancestry, a genetic risk score for adulthood obesity was generated for mothers (mGRS) and their babies (bGRS) as the weighted sum of BMI-increasing alleles of 97 single nucleotide polymorphisms known to be associated with BMI. The median GRS value was used as a cut-off to define high or low bGRS and mGRS. High bGRS was significantly associated with 70.9 g lower birthweight (95% Confidence Interval [CI]=-130.5 to -15.2) compared to low bGRS. mGRS was positively correlated with birthweight but the association was not significant. mGRS modified the significant birthweight-increasing effect of maternal pre-pregnancy BMI (P-for-interaction=0.03); among mothers with low mGRS, those who were overweight or obese had 138.3 g heavier babies (95% CI= 53.3 to 223.4) compared to those who had normal weight. These findings indicate that while offspring obesity genetic risk loci exert direct influence on birthweight, maternal obesity genetic risk loci modify the effect of pre-pregnancy BMI on birthweight. In all, the findings suggest that obesity polygenic risk may have potentially valuable information for preventing the trans-generational cycle of obesity.